Sintomas psicopatológicos e situação laboral de profissionais de enfermagem do sudeste brasileiro no contexto da pandemia de COVID-19 - Alves, Jheynny Sousa (2021)
Objective: To evaluate the relationship between psychopathological symptoms and the work situation of nursing professionals in the southeastern region, Brazil, in the context of the COVID-19 pandemic. Method: This is an observational and cross-sectional predictive study. The data were collected in the Southeast region of Brazil, digitally, during the period from April to June 2020. Nursing professionals were recruited through the snowball technique, the research instrument was made available on social networks (Facebook, WhatsApp) through a link with an invitation to participate in the research. The data collection instruments (questionnaires) could only be accessed if the participant agreed to participate voluntarily in the research. Namely, the instruments used were: questionnaire with sociodemographic and work information; Symptom Assessment Scale-40-R (SCL-40-R). The collected information was recorded in Excel spreadsheets. To perform the data analysis, the statistical program Statistical Package for the Social Science (SPSS), version 22, Kolmogorov-Smirnov test (to verify the distribution of data) was used, to analyze the association of variables, the test was used Mann Whitney's U for binary variables, while for multiple variables, the Kruskal-Wallis (KW) test was used. Results: 532 nursing professionals participated in the study. The average age was 37 years. Most participants are nurses. As for the association between the domains of the SCL-40-R scale and the participants' work data and social profile, an association was found between the following variables: age group and all domains of the scale; sex and the Psychoticism and Obsessiveness-compulsivity domains; weekly workload and the Psychotism domain; suffering from embarrassment and / or violence in the course of their work since the beginning of the COVID-19 pandemic and all domains of the scale; receiving psychological / emotional support from the institution where you work / study in the context of the COVID-19 pandemic and all domains of the scale. Conclusion: The study revealed that the mental health of nursing professionals, especially during the COVID-19 pandemic, should be investigated, as they are exposed to several factors that can cause mental illness. Thus, it is extremely important to carry out early psychological interventions with these professionals, with a view to ensuring their mental health. In addition, the creation of guidelines aimed at welcoming and monitoring professionals and the institutions' adherence to their psychological support, contributed to the increase of their psychological well-being, both in the period of the pandemic and in the period after it.